Radiolabeling Method for Lyophilizate for Dry Powder Inhalation Formulations - Kahori Miyamoto; Tomomi Akita; Chikamasa Yamashita (MDPI AG, 2022)
Human lung deposition data is non-mandatory for drug approval but very useful for the development of orally inhaled drug products. Lung deposition of inhaled drugs can be quantified by radionuclide imaging, for which one of the first considerations is the method used to radiolabel formulations. In this study, we report the development of a radiolabeling method for lyophilizate for dry powder inhalation (LDPI) formulations. TechneCoatTM is one method that can radiolabel drug particles without using solvents. In this method, particles are radiolabeled with a dispersion of 99mTc-labeled nanoparticles called TechnegasTM. Because a LDPI formulation is not comprised of particles but is a lyophilized cake aerosolized by air impact, the TechneCoat method cannot be used for the radiolabeling of LDPI formulations. We therefore modified the TechneCoat apparatus so that LDPI formulations were not aerosolized by the Technegas flow. Radiolabeling using a modified TechneCoat apparatus was validated with model LDPI formulations of interferon alpha (IFN). IFN of 99mTc-unlabeled, IFN of 99mTc-labeled, and 99mTc of 99mTc-labeled LDPI formulations showed similar behavior, and differences from IFN of 99mTc-unlabeled LDPI formulations were within ±15% in aerodynamic particle size distribution measurement. Our radiolabeling method for LDPI formulations may be useful for the quantification of drug deposition in human lungs.